(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To assess the efficacy of a photomyostimulation method in treatment of patients with stage III (advanced) primary open angle glaucoma (POAG) with drug-compensated intraocular pressure. Material and Methods: 18 patients with POAG were examined. Treatment was performed using an ophthalmic photomyostimulation unit (FMS-1). The treatment course consisted of 10 sessions. The duration of the session was 10 minutes with patient’s optimal impulse movement frequency (IMF) in a chaotic mode under scotopic conditions. The treatment success was assessed according to changes in functional mobility of the oculomotor system on the ground of IMF values and in lability of the visual system according to critical flicker fusion frequency (CFFF), Hz, and critical flicker appearance frequency (CFAF), Hz. Also, computed static perimetry and tonography data were assessed. Results: The IMF values in horizontal, vertical and chaotic modes significantly increased after treatment, however, remained far below the norm. The CFFF index of visual system lability both in the static mode and in three kinetic modes (horizontal, vertical, and chaotic) significantly increased after treatment to the norm. The similar changes were noted when studying the lability of the visual system according to the CFAF values in the static and three kinetic modes. The treatment performed resulted in improving the hydrodynamics of the eye. Thus, the facility of aqueous outflow increased by 31.2%, a Ро/С coefficient decreased by 20.0%, and the rate of aqueous flow increased by 35.5%. The mean deviation of light sensitivity (MD) significantly increased by 7.3% and the mean retinal light sensitivity (MS) according to all MS threshold values significantly increased by 8.8% as well. Summarized visual field according to eight quadrants was enlarged after treatment by 12.0%. Conclusions: The data obtained give the evidence that the photomyostimulation method is highly successful in the treatment of patients with stage III POAG and can be included in a therapy of such patients.